PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT KAMPUNG KEARIFAN INDONESIA JAKARTA SELATAN - Eka Ramadhanthi, Annisa; Ma’fiyah (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of work environment and work discipline on employee performance at PT Kampung Kearifan Indonesia South Jakarta partially and simultaneously. The population amounted to 104 people who were processed using the slovin formula so as to get a total of 83 respondents to be submitted as sampling subjects. The method used is quantitative associative. Data analysis uses instrument tests, classic assumption tests, and quantitative analysis. The results showed that the work environment had a significant effect on employee performance with the regression equation Y = 20.881 + 2.441X1, the correlation coefficient value of 0.496, the coefficient of determination of 24.6%. Hypothesis testing obtained a t value of 5.314> t table 1.990. Thus H0 is rejected and H1 is accepted, which means there is a significant influence. Work discipline has a significant effect on employee performance with the regression equation Y = 14.095 + 2.638X2, the correlation coefficient is 39.9%. Hypothesis testing obtained t value 7.329> t table 1.990. Thus H0 is rejected with H2 accepted, meaning that there is a significant partial influence between work discipline on employee performance. The work environment and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 10.831 + 0.206X1 + 0.483X2, the correlation coefficient of 0.679 means that the two variables have a strong level of relationship. With a coefficient of determination of 46.1%. Hypothesis testing obtained the value of f count 34,187> f table 2,720. Thus H0 is rejected and H3 is accepted, meaning that there is a simultaneous significant influence between the work environment and work discipline on employee performance.